PENJATUHAN SANKSI PIDANA KUMULASI UANG PENGGANTI KEPADA PELAKU TINDAK PIDANA KORUPSI: Imposition Of Cumulation Criminal Sanctions For The Compensation Money To The Perpetrator Of Corruption - Trisya Hutami; Ermania Widjajanti (Universitas Trisakti, 2024)
From 2017 through 2021, Indonesia, the world's fourth-most corrupt nation, would incur massive state losses amounting to Rp 170,388 trillion. Only Rp. 1.4 trillion, or around 2.2% of the total state losses incurred by corruption cases, have been restored to the state via the provision of further penalty in the form of replacement money. Normative judicial, descriptive analytical, secondary data with literature study, and qualitative research methods are used. A replacement monetary penalty, in this case assumed to be a prison term of 2 (two) years, has been imposed, despite the fact that it is disproportionate to the amount of state losses incurred and the perpetrator's personal wealth felt and is therefore unlikely to fully recover losses to state finances. Therefore, the imposition of cumulative sanctions in the form of principal punishment (imprisonment and fines) and additional punishment (compensation money) should be paid in full until the state's financial losses are recovered, so that the imposition of cumulative criminal sanctions becomes effective in nature.